Mali Financial Sector Assessment Program : The Insurance Sector - World Bank Group (World Bank, Washington, DC, 2016)
This note summarizes the findings and conclusions of the review of the insurance sector in Mali. The review was conducted as part of the 2015 financial sector assessment program (FSAP) in Mali. The main objectives of the review are to assess the structure, performance, and outlook of the insurance sector with respect to the potential for the sector to develop; and to contribute to the overall long term growth and development of the economy and the well-being of the country's population. The insurance market in Mali falls short of its potential today; however, its outlook is promising. This technical note looks at two questions: what role does the insurance sector play in Mali today?, and how can it play a more significant role? It highlights the potential of micro insurance and agriculture insurance in particular, and concludes with a number of recommendations.